Workplace Bullying and Its Associated Factors Among Medical Doctors in Residency Training in a Tertiary Health Institution in Plateau State Nigeria - Afolaranmi, Tolulope O.; Hassan, Zuwaira I.; Gokir, Benjamin M.; Kilani, Abdulrahman; Igboke, Raphael; Ugwu, Kainechukwu G.; Amaike, Chikwendu; Ofakunrin, Akinyemi O. D. (Frontiers in Public Health, 2022)
Background: Bullying is a public health problem globally in workplaces with untold deleterious effects on the health and well-being of individuals at the receiving end. Bullying has been found to disrupt social interaction at workplace thereby creating an unhealthy and seemingly unproductive work environment. Studies have reported varying rates of workplace bullying as high as 83% in Europe, 65% in the Americas and 55% in Asia with very little documented in the contemporary African setting and Nigeria in particular. It therefore became imperative to assess the level of bullying, its form and predictors among medical doctors in residency training in a tertiary health institution in Plateau state Nigeria. Methodology: This was a cross sectional study conducted among resident doctors in Jos University Teaching Hospital between November 2019 and February 2020 using quantitative method of data collection and SPSS version 20 was used for data analysis. Crude and adjusted odds ratios as well as 95% confidence interval were used in this study with a p-value of ≤ 0.05 considered statistically significant. Results: The mean age of the respondents was 32.3 ± 3.9 years with 78 (62.9%) being 31 years and above. Bullying was currently being experienced by 74 (59.7%) of the respondents with verbal aggression and threats, insult and use of derogatory remarks being forms of bullying experienced by 85.1% and 74.3% of the respondents respectively while not witnessing a colleague being bullied was its significant predictor (AOR = 0.18; 95% CI = 0.068 – 0.449; p < 0.001). Conclusion: Workplace bullying has been found to be in existence and relatively high among medical doctors in residency training in this setting with witnessing someone being bullied as its sole predictor.